Theory and practice of law and music: two improvisations - Delgado Echeverría, Jesús (Revista de derecho aragonés, 2024)
The two papers that I present under a joint title were born at different times, but their content responds to the same purpose: to show that legal theory can learn a lot from music theory (I suppose also the other way around). Specifically, that any theory that matters is a theory of a practice. In the first, more general one, I have explored some of the features of legal and musical interpretation that allow for a joint or analogical analysis: especially, the fact that the interpretation takes place in a time, always the present, and in a specific geographical and social place; and that it is regularly produced by specialized groups or ensembles, with their specific repertoire and their own interpretative traditions. The second deals with some features of the regulation and practice of compensation for damages, which challenge the mould of codified rules; it seems suggestive to evoke, in order to try to understand this important phenomenon in the world of law, jazz music and its elusive relationship with conventional music scores.